High-strength glass fiber reinforced plastic for composite cylindrical shell and preparation method of high-strength glass fiber reinforced plastic

By introducing specific elements and structures into epoxy resin and combining them with raw materials such as glass fiber, the insufficient performance problem of existing glass fiber reinforced plastics in high-end application scenarios is solved, and the high strength, good flame retardant, acid and alkali resistance and heat resistance of composite materials are achieved.

CN119775715AInactive Publication Date: 2025-04-08XINXIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510278907.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In high-end application scenarios, the existing glass fiber reinforced plastics used in composite cylindrical shells have problems such as insufficient strength, insufficient flame retardant performance and poor high temperature resistance in high-temperature performance, resulting in safety hazards in the equipment.

Method used

By introducing silicone, nitrogen, benzene ring and sulfone groups into the molecular structure of the epoxy resin, modifying epoxy resin is prepared, and compounded with alkali-free glass fiber, kaolin, talc powder, nano-silica and other raw materials, the comprehensive performance of the plastic is significantly improved.

Benefits of technology

It significantly improves the flame retardant properties, mechanical properties, acid and alkali corrosion resistance and heat resistance of composite materials, meets the demand for high-performance composite materials in high-end application scenarios, and reduces the safety hazards of equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention belongs to the technical field of glass fiber reinforced plastics, and particularly relates to a high-strength glass fiber reinforced plastic for a composite cylindrical shell and a preparation method of the high-strength glass fiber reinforced plastic. The plastic is prepared from the following raw materials in parts by weight: 50 to 70 parts of modified epoxy resin, 20 to 30 parts of glass fiber, 5 to 10 parts of filler, 1 to 3 parts of coupling agent, 3 to 5 parts of initiator and 1 to 3 parts of antioxidant. The modified epoxy resin is prepared by a three-step method, and organic silicon, a nitrogen element, a benzene ring and sulfuryl are introduced into the molecular structure of the epoxy resin; and the modified epoxy resin is compounded with the alkali-free glass fiber, kaolin and other raw materials, so that the plastic performance is comprehensively optimized, and the flame retardance, mechanical property, acid and alkali corrosion resistance and heat resistance of the plastic are remarkably improved from molecular structure design to composite enhancement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass fiber reinforced plastics, and in particular relates to a high-strength glass fiber reinforced plastic for a composite material cylindrical shell and a preparation method thereof. Background Art

[0002] Composite cylindrical shells have been widely used in many fields such as aerospace, shipbuilding, and automobiles due to their many advantages such as light weight and high strength. In these application scenarios, there are extremely stringent requirements on the strength and other properties of composite cylindrical shells. Traditional composite materials are often difficult to meet the requirements when facing some special working conditions or high performance requirements. Glass fiber reinforced plastics, as a common composite material, are widely used in industrial production due to their high specific strength and good corrosion resistance. However, the strength of existing glass fiber reinforced plastics used for composite cylindrical shells still needs to be further improved in some high-end application scenarios. For example, in the petrochemical production environment, leaked flammable gases or liquids can easily cause fires and explosions. The cylindrical shells of petrochemical equipment require flame retardant properties to prevent the spread of fire, but the existing glass fiber reinforced plastics will lose strength due to the erosion of chemicals and the combined action of high-temperature flames when encountering chemical fires, resulting in safety hazards in the equipment. Therefore, it is of great practical significance to develop a high-strength glass fiber reinforced plastic for composite cylindrical shells, which can effectively solve the problem of insufficient performance of existing materials in high-end application scenarios and meet the urgent needs of related fields for high-performance composite materials.

[0003] The patent with application number CN202211095210.4 provides a glass fiber reinforced composite plastic, which is made of multiple raw materials such as synthetic resin, alkali-free glass fiber, polycarbonate, etc. in a specific proportion. The preparation process of the alkali-free glass fiber is: stirring the raw materials, melting, drawing, coating, and removing impurities to obtain the obtained material; the invention greatly increases the toughness of the plastic, improves its service life, and effectively prevents oxidation by adding alkali-free glass fiber to the raw materials of the plastic. Compared with conventional composite plastics, the product prepared by this invention has significant effect in improving strength and toughness. However, its high temperature resistance is not good. Under high temperature conditions, organic components such as synthetic resin and polycarbonate are prone to softening, degradation, or even decomposition, which will cause the mechanical properties of the composite material to drop sharply, causing it to lose its original structural stability and functionality. The patent with application number CN202110136392.4 provides a glass fiber reinforced plastic and a preparation method thereof, wherein the glass fiber reinforced plastic is made of bisphenol A type unsaturated polyester resin, antioxidant, talcum powder and other raw materials, wherein the antioxidant is prepared by mixing antioxidant 215 and antioxidant 330 in a ratio of 3:5; when preparing the plastic, the raw materials are first weighed by weight, and then the temperature and speed are controlled in stages, and finally cooled and extruded for granulation; the invention greatly improves the high temperature resistance of the product by reasonably proportioning the raw materials, so that it maintains good strength, corrosion resistance and impact resistance in a high temperature environment. However, its flame retardant performance is insufficient. In fields with high requirements for fire safety such as building fire protection, electronic appliances, transportation, etc., once a fire occurs, this material that lacks flame retardancy will burn rapidly, not only failing to effectively prevent the spread of the fire, but also releasing a large amount of toxic smoke, posing a huge threat to the safety of life and property. Summary of the invention

[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a high-strength glass fiber reinforced plastic for composite cylindrical shells and a preparation method thereof, by introducing organic silicon, nitrogen elements, benzene rings and sulfone groups into the molecular structure of epoxy resin to obtain modified epoxy resin, and compounding it with raw materials such as alkali-free glass fiber, kaolin, talcum powder, nano-silicon dioxide, etc., which significantly improves the comprehensive performance of plastics. Through a series of modification and compounding measures, from molecular structure design to composite reinforcement of materials, plastics are optimized in all directions, which not only improves the flame retardant properties, mechanical properties, acid and alkali corrosion resistance and heat resistance of the materials, but also opens up a broader space for them in industrial applications.

[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A high-strength glass fiber reinforced plastic for composite cylindrical shells, comprising the following raw materials in parts by weight: 50-70 parts of modified epoxy resin, 20-30 parts of glass fiber, 5-10 parts of filler, 1-3 parts of coupling agent, 3-5 parts of initiator, and 1-3 parts of antioxidant; The preparation method of the modified epoxy resin is: S1. Under stirring conditions, 2-methyl-4-methylsulfonylbenzoic acid, chromium acetate and cyclohexane were mixed evenly, and 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise within 30-50 minutes. The temperature was raised to 75-85°C, and the reaction was carried out for 8-10 hours. After cooling, the intermediate 1 was purified to obtain the structural formula of the intermediate 1: ; S2. Under stirring conditions, 3-amino-3-methylbutyric acid and the intermediate 1 obtained in step S1 are dispersed in N,N-dimethylformamide, and p-toluenesulfonic acid is added. The temperature is raised to 60-80° C., and the reaction is carried out for 10-12 hours. The intermediate 2 is purified after cooling to obtain the intermediate 2. The structural formula of the intermediate 2 is: ; S3, heating tetrahydrofuran to 50-60°C, adding epoxy resin, stirring for 20-40min, then adding intermediate 2 obtained in step S2, raising the temperature to 65-85°C, continuing stirring for 6-9h, cooling and removing the solvent to obtain a modified epoxy resin; Among them, the synthetic route of intermediate 2 is as follows: ; .

[0006] The present invention uses 2-methyl-4-methylsulfonylbenzoic acid and 3-(2,3-epoxypropoxy)propyltrimethoxysilane as starting materials, and performs an epoxy compound ring-opening reaction under the catalytic action of chromium acetate to obtain an intermediate 1; then uses the intermediate 1 and 3-amino-3-methylbutyric acid as raw materials, and performs an esterification reaction under the action of p-toluenesulfonic acid to obtain an intermediate 2; finally, uses the intermediate 2 as a modifier, and performs chemical grafting on an epoxy resin under heating conditions to obtain a modified epoxy resin.

[0007] In order to functionalize the epoxy resin, the molar ratio of 2-methyl-4-methylsulfonylbenzoic acid, chromium acetate, and 3-(2,3-epoxypropoxy)propyltrimethoxysilane in step S1 is 1.1:0.015-0.025:1.1-1.4, and the mass volume ratio of 2-methyl-4-methylsulfonylbenzoic acid to cyclohexane is 0.16-0.24 g / mL; the molar ratio of 3-amino-3-methylbutyric acid, intermediate 1, and p-toluenesulfonic acid in step S2 is 1.3:0.9-1.1:0.019-0.026, and the amount of 3-amino-3-methylbutyric acid added to the N,N-dimethylformamide is 0.11-0.18 g / mL; the mass ratio of the epoxy resin and the intermediate 2 in step S3 is 100:10-15, and the amount of the epoxy resin added to the tetrahydrofuran is 1-2 g / mL.

[0008] Furthermore, the glass fiber is an alkali-free glass fiber with a fiber length of 3.0-4.5 mm; the filler is prepared by mixing kaolin, talc and nano-silica, and the mass ratio of kaolin, talc and nano-silica is 1-3:1-3:0.5; the initiator is prepared by mixing tert-butyl peroxide-2-ethylhexanoate and tert-butyl perbenzoate, and the mass ratio of tert-butyl peroxide-2-ethylhexanoate and tert-butyl perbenzoate is 1:1-3; the coupling agent is silane coupling agent KH550 or silane coupling agent KH560; the antioxidant is antioxidant 1010 or antioxidant 1076.

[0009] The present invention also provides a method for preparing high-strength glass fiber reinforced plastic for composite cylindrical shells, comprising the following steps: heating a modified epoxy resin to 120-150°C, stirring at 800-1000rpm for 1-2h, then cooling to 60-80°C, adding an antioxidant and a coupling agent, stirring at 800-1200rpm for 20-40min, then adding a filler and an initiator, continuing to stir at 1100-1300rpm for 30-50min, then raising the temperature to 150-170°C, adding glass fiber, stirring at 600-800rpm for 1-2h, and extruding with a screw extruder to obtain the high-strength glass fiber reinforced plastic.

[0010] The present invention has the following beneficial effects: The present invention uses a three-step method to prepare a modified epoxy resin, and introduces organic silicon, nitrogen, benzene rings, and sulfone groups into the molecular structure of the epoxy resin. The introduction of organic silicon and nitrogen can play a synergistic role in improving the flame retardant properties of composite materials; organic silicon can form a dense carbonized protective film at high temperatures, which can effectively prevent the transfer of heat and oxygen, thereby slowing down the burning speed of the material; the presence of nitrogen enhances the self-extinguishing property of the material, and the material can quickly stop burning when the flame leaves; the dual effects of organic silicon and nitrogen make the polymer material have good flame retardant properties when facing the threat of fire, thereby improving the flame retardant properties of composite plastics. The introduction of benzene ring structure gives epoxy resin a double improvement in rigidity and thermal stability. As a relatively rigid aromatic structure, the existence of benzene ring is like adding many tiny skeletons to the polymer molecule, which makes the material show higher mechanical strength on a macro scale. In terms of heat resistance, benzene ring can effectively hinder the thermal motion of molecules, so that the polymer material can still maintain a stable structure at high temperature, thereby improving the overall heat resistance of the material. Benzene ring enhances the rigidity and thermal stability of the material, providing a solid skeleton structure for the composite material, while glass fiber, with its high strength characteristics, provides additional tensile strength and bending strength for the composite material. The two cooperate with each other to build a strong support network inside the composite material, which enables the composite material to maintain good mechanical properties when subjected to various external forces. The sulfone group reacts with the active sites in the acid-base medium to form a stable chemical bond, and builds a chemical protective layer on the surface of the composite material. Nano-silicon dioxide further improves the density of the material through its filling effect and reduces the channel for the penetration of acid-base medium. The two complement each other and work together to significantly improve the acid-base corrosion resistance of the composite material. In addition, silicone can form stable chemical bonds inside the material, which can effectively prevent the thermal motion of molecules and further improve the thermal stability of the material.

[0011] The present invention compounds the modified epoxy resin with raw materials such as alkali-free glass fiber, kaolin, talcum powder, nano-silicon dioxide, etc., which significantly improves the flame retardant properties, mechanical properties, acid and alkali corrosion resistance and heat resistance of the plastic. DETAILED DESCRIPTION

[0012] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0013] Epoxy resin, solid content 99.5%, grade E-44, brand Baling Petrochemical; kaolin, mesh number 1250 mesh, effective content 98%, whiteness 94%, purchased from Hebei Huishun Mining Co., Ltd.; talcum powder, silicon dioxide content 60%, magnesium oxide content 30%, fineness 600 mesh, purchased from Lingshou County Yongshun Mineral Products Processing Plant; nano silicon dioxide, effective ingredient content 99.9%, fineness 10 microns, pH value 5.0-8.0, purchased from Lingshou County Baiyi Mineral Products Processing Plant; glass fiber, specific gravity 2.68g / cm³, diameter 13um, purchased from Taian Haosong Fiber Co., Ltd. The raw materials used in the following examples are all common commercially available products. Example 1

[0014] A high-strength glass fiber reinforced plastic for composite cylindrical shells, comprising the following raw materials in parts by weight: 60 parts of modified epoxy resin, 25 parts of glass fiber, 8 parts of filler, 2 parts of coupling agent, 4 parts of initiator, and 2 parts of antioxidant; wherein the glass fiber is alkali-free glass fiber, and the fiber length is 3.0 mm; the filler is prepared by mixing kaolin, talcum powder, and nano-silicon dioxide, and the mass ratio of kaolin, talcum powder, and nano-silicon dioxide is 2:2:0.5; the initiator is prepared by mixing tert-butyl peroxide-2-ethylhexanoate and tert-butyl peroxide benzoate, and the mass ratio of tert-butyl peroxide-2-ethylhexanoate and tert-butyl peroxide benzoate is 1:2; the coupling agent is silane coupling agent KH550; the antioxidant is antioxidant 1010; The preparation method of the modified epoxy resin is: S1. Under stirring conditions, 2-methyl-4-methylsulfonylbenzoic acid, chromium acetate and cyclohexane are uniformly mixed, 3-(2,3-epoxypropoxy)propyltrimethoxysilane is added dropwise, and the addition is completed within 40 minutes. The temperature is raised to 80°C, refluxed for 9 hours, naturally cooled to room temperature, filtered, the filtrate is taken, ethyl acetate is added for extraction, liquid separation is performed, an ester layer is obtained, and after reduced pressure distillation, vacuum drying is performed to constant weight to obtain intermediate 1; wherein the molar ratio of the 2-methyl-4-methylsulfonylbenzoic acid, chromium acetate and 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 1.1:0.02:1.3, and the mass volume ratio of the 2-methyl-4-methylsulfonylbenzoic acid to cyclohexane is 0.2 g / mL; S2. Disperse 3-amino-3-methylbutyric acid and the intermediate 1 obtained in step S1 in N,N-dimethylformamide under stirring, add p-toluenesulfonic acid, heat to 70°C, reflux for 11 hours, cool naturally to room temperature, add deionized water and ethyl acetate for extraction, the volume ratio of N,N-dimethylformamide, deionized water and ethyl acetate is 1:1:2, separate the liquids to obtain an ester layer, wash it with a saturated sodium chloride solution, and then dry it with anhydrous sodium sulfate, distill it under reduced pressure, and vacuum dry it to constant weight to obtain intermediate 2; wherein the molar ratio of the 3-amino-3-methylbutyric acid, the intermediate 1 and p-toluenesulfonic acid is 1.3:1:0.022, and the amount of 3-amino-3-methylbutyric acid added to the N,N-dimethylformamide is 0.15 g / mL; The NMR results of intermediate 2 are: 1 H NMR (300MHz, DMSO-d6) δ 8.52 (s, 2H), 8.30 (d, 1H), 7.81 (d, 2H), 5.46 (t, 1H), 4.59 (d, 1H), 4.32 (d, 1H), 3.72 (d, 1H), 3.47-3.5 3 (m, 10H), 3.32-3.35 (t, 5H), 2.48 (s, 3H), 2.39 (s, 2H), 1.41-1.45 (m, 2H), 1.27 (s, 6H), 0.56 (t, 2H); S3, heating tetrahydrofuran to 55 ° C, adding epoxy resin, stirring for 30 min, then adding intermediate 2 obtained in step S2, raising the temperature to 75 ° C, continuing stirring for 8 h, naturally cooling to room temperature, removing tetrahydrofuran by reduced pressure distillation, and vacuum drying to constant weight to obtain a modified epoxy resin; wherein the mass ratio of the epoxy resin to the intermediate 2 is 100:13, and the amount of epoxy resin added to the tetrahydrofuran is 1.5 g / mL.

[0015] A preparation method of high-strength glass fiber reinforced plastic for composite cylindrical shells comprises the following steps: heating a modified epoxy resin to 140°C, stirring at 900 rpm for 1.5 hours, then cooling to 70°C, adding an antioxidant and a coupling agent, stirring at 1000 rpm for 30 minutes, then adding a filler and an initiator, stirring at 1200 rpm for 40 minutes, then raising the temperature to 160°C, adding glass fiber, stirring at 700 rpm for 1.5 hours to obtain a premix, cooling the premix naturally to 120-125°C, then conveying the premix to a screw extruder for extrusion, and cooling naturally to room temperature to obtain the premix; wherein the extruder is a single screw extruder, the temperature of the front section of the extruder is 120-125°C, the temperature of the rear section is 125-130°C, and the temperature of the die head is 130-140°C. Example 2

[0016] A high-strength glass fiber reinforced plastic for composite cylindrical shells, comprising the following raw materials in parts by weight: 50 parts of modified epoxy resin, 20 parts of glass fiber, 5 parts of filler, 1 part of coupling agent, 3 parts of initiator, and 1 part of antioxidant; wherein the glass fiber is alkali-free glass fiber, and the fiber length is 4.5 mm; the filler is prepared by mixing kaolin, talcum powder, and nano-silicon dioxide, and the mass ratio of kaolin, talcum powder, and nano-silicon dioxide is 1:1:0.5; the initiator is prepared by mixing tert-butyl peroxide-2-ethylhexanoate and tert-butyl perbenzoate, and the mass ratio of tert-butyl peroxide-2-ethylhexanoate and tert-butyl perbenzoate is 1:1; the coupling agent is silane coupling agent KH560; the antioxidant is antioxidant 1010; The preparation method of the modified epoxy resin is: S1. Under stirring conditions, 2-methyl-4-methylsulfonylbenzoic acid, chromium acetate and cyclohexane are uniformly mixed, 3-(2,3-epoxypropoxy)propyltrimethoxysilane is added dropwise, and the addition is completed within 40 minutes. The temperature is raised to 75°C, refluxed for 10 hours, naturally cooled to room temperature, filtered, the filtrate is taken, ethyl acetate is added for extraction, liquid separation is performed, an ester layer is obtained, and after reduced pressure distillation, vacuum drying is performed to constant weight to obtain intermediate 1; wherein the molar ratio of the 2-methyl-4-methylsulfonylbenzoic acid, chromium acetate and 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 1.1:0.025:1.4, and the mass volume ratio of the 2-methyl-4-methylsulfonylbenzoic acid to cyclohexane is 0.24 g / mL; S2. Under stirring conditions, 3-amino-3-methylbutyric acid and the intermediate 1 obtained in step S1 are dispersed in N,N-dimethylformamide, and p-toluenesulfonic acid is added. The temperature is raised to 60°C, and the reaction is refluxed for 12 hours. The mixture is naturally cooled to room temperature, and deionized water and ethyl acetate are added for extraction. The volume ratio of N,N-dimethylformamide, deionized water and ethyl acetate is 1:1:2. The ester layer is separated to obtain an ester layer. The ester layer is first washed with a saturated sodium chloride solution, and then dried with anhydrous sodium sulfate. The ester layer is distilled under reduced pressure and dried in vacuo to a constant weight to obtain an intermediate 2. The molar ratio of the 3-amino-3-methylbutyric acid, the intermediate 1 and p-toluenesulfonic acid is 1.3:1.1:0.026, and the amount of 3-amino-3-methylbutyric acid added to the N,N-dimethylformamide is 0.18 g / mL. S3, heating tetrahydrofuran to 50 ° C, adding epoxy resin, stirring for 40 min, then adding intermediate 2 obtained in step S2, raising the temperature to 65 ° C, continuing stirring for 9 h, naturally cooling to room temperature, removing tetrahydrofuran by reduced pressure distillation, and vacuum drying to constant weight to obtain a modified epoxy resin; wherein the mass ratio of the epoxy resin to the intermediate 2 is 100:15, and the amount of epoxy resin added to the tetrahydrofuran is 2 g / mL.

[0017] A preparation method of high-strength glass fiber reinforced plastic for composite cylindrical shells comprises the following steps: heating a modified epoxy resin to 120°C, stirring at 1000 rpm for 2 hours, then cooling to 60°C, adding an antioxidant and a coupling agent, stirring at 1200 rpm for 40 minutes, then adding a filler and an initiator, stirring at 1300 rpm for 50 minutes, then raising the temperature to 150°C, adding glass fiber, stirring at 800 rpm for 2 hours to obtain a premix, naturally cooling the premix to 120-125°C, then conveying the premix to a screw extruder for extrusion, and naturally cooling to room temperature to obtain the premix; wherein the extruder is a single screw extruder, the temperature of the front section of the extruder is 120-125°C, the temperature of the rear section is 125-130°C, and the temperature of the die head is 130-140°C. Example 3

[0018] A high-strength glass fiber reinforced plastic for composite cylindrical shells, comprising the following raw materials in parts by weight: 70 parts of modified epoxy resin, 30 parts of glass fiber, 10 parts of filler, 3 parts of coupling agent, 5 parts of initiator, and 3 parts of antioxidant; wherein the glass fiber is alkali-free glass fiber, and the fiber length is 3.0 mm; the filler is prepared by mixing kaolin, talcum powder, and nano-silicon dioxide, and the mass ratio of kaolin, talcum powder, and nano-silicon dioxide is 3:3:0.5; the initiator is prepared by mixing tert-butyl peroxide-2-ethylhexanoate and tert-butyl perbenzoate, and the mass ratio of tert-butyl peroxide-2-ethylhexanoate and tert-butyl perbenzoate is 1:3; the coupling agent is silane coupling agent KH550; the antioxidant is antioxidant 1076; The preparation method of the modified epoxy resin is: S1. Under stirring conditions, 2-methyl-4-methylsulfonylbenzoic acid, chromium acetate and cyclohexane were mixed evenly, 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise, and the addition was completed within 30 minutes. The temperature was raised to 85°C, refluxed for 8 hours, naturally cooled to room temperature, filtered, and the filtrate was taken. Ethyl acetate was added for extraction, and the ester layer was obtained. After reduced pressure distillation, vacuum drying was performed to constant weight to obtain intermediate 1; wherein the molar ratio of the 2-methyl-4-methylsulfonylbenzoic acid, chromium acetate and 3-(2,3-epoxypropoxy)propyltrimethoxysilane was 1.1:0.015:1.1, and the mass volume ratio of the 2-methyl-4-methylsulfonylbenzoic acid to cyclohexane was 0.16 g / mL; S2. Under stirring conditions, 3-amino-3-methylbutyric acid and the intermediate 1 obtained in step S1 are dispersed in N,N-dimethylformamide, and p-toluenesulfonic acid is added. The temperature is raised to 80°C, and the reaction is refluxed for 10 hours. The mixture is naturally cooled to room temperature, and deionized water and ethyl acetate are added for extraction. The volume ratio of N,N-dimethylformamide, deionized water and ethyl acetate is 1:1:2. The ester layer is separated to obtain an ester layer. The ester layer is first washed with a saturated sodium chloride solution, and then dried with anhydrous sodium sulfate. The ester layer is distilled under reduced pressure and dried in vacuo to a constant weight to obtain an intermediate 2. The molar ratio of the 3-amino-3-methylbutyric acid, the intermediate 1 and p-toluenesulfonic acid is 1.3:0.9:0.019, and the amount of 3-amino-3-methylbutyric acid added to the N,N-dimethylformamide is 0.11 g / mL. S3, heating tetrahydrofuran to 60 ° C, adding epoxy resin, stirring for 20 min, then adding intermediate 2 obtained in step S2, raising the temperature to 85 ° C, continuing stirring for 6 h, naturally cooling to room temperature, removing tetrahydrofuran by distillation under reduced pressure, and vacuum drying to constant weight to obtain a modified epoxy resin; wherein the mass ratio of the epoxy resin to the intermediate 2 is 100:10, and the amount of epoxy resin added to the tetrahydrofuran is 1 g / mL.

[0019] A preparation method of high-strength glass fiber reinforced plastic for composite cylindrical shells comprises the following steps: heating a modified epoxy resin to 150°C, stirring at 800 rpm for 1 hour, then cooling to 80°C, adding an antioxidant and a coupling agent, stirring at 800 rpm for 20 minutes, then adding a filler and an initiator, stirring at 1100 rpm for 30 minutes, then raising the temperature to 170°C, adding glass fiber, stirring at 600 rpm for 1 hour to obtain a premix, cooling the premix naturally to 120-125°C, then conveying the premix to a screw extruder for extrusion, and cooling naturally to room temperature to obtain the premix; wherein the extruder is a single screw extruder, the temperature of the front section of the extruder is 120-125°C, the temperature of the rear section is 125-130°C, and the temperature of the die head is 130-140°C. Example 4

[0020] A high-strength glass fiber reinforced plastic for a composite cylindrical shell comprises the following raw materials in parts by weight: 65 parts of a modified epoxy resin, 22 parts of glass fiber, 7 parts of a filler, 2.5 parts of a coupling agent, 3.5 parts of an initiator, and 1.5 parts of an antioxidant; the rest is the same as in Example 1.

[0021] A method for preparing high-strength glass fiber reinforced plastic for composite cylindrical shells is prepared according to the method described in Example 1. Comparative Example 1

[0022] A high-strength glass fiber reinforced plastic for a composite cylindrical shell comprises the following raw materials in parts by weight: 35 parts of modified epoxy resin, 35 parts of glass fiber, 3 parts of filler, 2 parts of coupling agent, 2 parts of initiator, and 3 parts of antioxidant; the rest is the same as in Example 1.

[0023] A method for preparing high-strength glass fiber reinforced plastic for composite cylindrical shells is prepared according to the method described in Example 1.

[0024] In the examples, the weight percentage of the modified epoxy resin is significantly higher than that of the glass fiber. This comparative example mainly adjusts the weight percentages of the modified epoxy resin and the glass fiber, and the other components are also adaptively adjusted. Comparative Example 2

[0025] A high-strength glass fiber reinforced plastic for a composite cylindrical shell comprises the following raw materials in parts by weight: 65 parts of epoxy resin, 30 parts of glass fiber, 8 parts of filler, 3 parts of coupling agent, 4 parts of initiator, and 2 parts of antioxidant; the rest is the same as in Example 1.

[0026] A method for preparing high-strength glass fiber reinforced plastic for composite cylindrical shells is prepared according to the method described in Example 1.

[0027] Based on the types and amounts of raw materials in the examples, this comparative example used epoxy resin instead of modified epoxy resin for a comparative experiment. The amount was dynamically adjusted according to actual conditions. Multiple groups of comparative experiments were conducted, and the group with better performance was selected as comparative example 2.

[0028] The high-strength glass fiber reinforced plastics prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to relevant performance tests. The oxygen index test was conducted in accordance with GB / T8924-2005 "Fiber-reinforced Plastic Combustion Performance Test Method Oxygen Index Method"; the tensile strength test was conducted in accordance with GB / T 1040-2006 "Determination of tensile properties of plastics", the sample size is 150mm×10mm×2mm, the universal tensile testing machine is used, the test speed is 2mm / min, the tensile strength of the sample before and after aging is tested, the aging conditions are: placed at 200℃ for 7d, and the surface state of the sample after aging treatment (heat resistance) is observed; acid resistance test: the sample is immersed in a 10% sulfuric acid aqueous solution for 7d, the test temperature is 25℃, and the surface state of the sample is observed; alkali resistance test: the sample is immersed in a 10% sodium hydroxide aqueous solution for 7d, the test temperature is 25℃, and the surface state of the sample is observed; impact resistance test is carried out in accordance with GB / T1043.1-2008 "Determination of impact properties of simply supported beams of plastics", the sample size is 100mm×3mm×10mm, the notch width is 2mm, a plastic pendulum impact testing machine is used, and the impact energy is 75J; flame retardant performance test is carried out according to UL-94 standard method; the above tests are repeated three times and the average value is taken. The test results are shown in Table 1. It can be seen from the data in Table 1 that, compared with Comparative Examples 1-2, the glass fiber reinforced plastics prepared in Examples 1-4 have excellent flame retardant properties, mechanical properties, acid and alkali corrosion resistance and heat resistance; it can be seen from the data in Example 1 and Comparative Examples 1-2 that modifying the epoxy resin and optimizing the ratio of raw materials such as the modified epoxy resin, glass fiber, and filler can significantly improve the comprehensive performance of the composite material.

[0029] Table 1 Test results of relevant properties of high-strength glass fiber reinforced plastics used for composite cylindrical shells

[0030] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A high-strength glass fiber reinforced plastic for composite cylindrical shells, characterized in that: The invention comprises the following raw materials in parts by weight: 50-70 parts of modified epoxy resin, 20-30 parts of glass fiber, 5-10 parts of filler, 1-3 parts of coupling agent, 3-5 parts of initiator and 1-3 parts of antioxidant; The preparation method of the modified epoxy resin is: S1. Under stirring conditions, 2-methyl-4-methylsulfonylbenzoic acid, chromium acetate and cyclohexane were mixed evenly, and 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added dropwise within 30-50 minutes. The temperature was raised to 75-85°C, and the reaction was carried out for 8-10 hours. After cooling, the intermediate 1 was purified to obtain the intermediate 1. S2, under stirring conditions, dispersing 3-amino-3-methylbutyric acid and the intermediate 1 obtained in step S1 in N,N-dimethylformamide, adding p-toluenesulfonic acid, heating to 60-80° C., reacting for 10-12 hours, cooling and purifying to obtain intermediate 2; S3, heat tetrahydrofuran to 50-60°C, add epoxy resin, stir for 20-40min, then add intermediate 2 obtained in step S2, raise the temperature to 65-85°C, continue stirring for 6-9h, cool down and remove the solvent to obtain modified epoxy resin.

2. The high-strength glass fiber reinforced plastic for composite cylindrical shell according to claim 1, characterized in that: The molar ratio of 2-methyl-4-methylsulfonylbenzoic acid, chromium acetate and 3-(2,3-epoxypropoxy)propyltrimethoxysilane in step S1 is 1.1:0.015-0.025:1.1-1.4, and the mass volume ratio of 2-methyl-4-methylsulfonylbenzoic acid to cyclohexane is 0.16-0.24 g / mL.

3. The high-strength glass fiber reinforced plastic for composite cylindrical shell according to claim 1, characterized in that: The molar ratio of 3-amino-3-methylbutyric acid, intermediate 1, and p-toluenesulfonic acid in step S2 is 1.3:0.9-1.1:0.019-0.026, and the amount of 3-amino-3-methylbutyric acid added to the N,N-dimethylformamide is 0.11-0.18 g / mL.

4. The high-strength glass fiber reinforced plastic for composite cylindrical shell according to claim 1, characterized in that: The mass ratio of the epoxy resin to the intermediate 2 in step S3 is 100:10-15, and the amount of the epoxy resin added to the tetrahydrofuran is 1-2 g / mL.

5. The high-strength glass fiber reinforced plastic for composite cylindrical shell according to claim 1, characterized in that: The glass fiber is alkali-free glass fiber, and the fiber length is 3.0-4.5 mm.

6. The high-strength glass fiber reinforced plastic for composite cylindrical shell according to claim 1, characterized in that: The filler is prepared by mixing kaolin, talcum powder and nano silicon dioxide, and the mass ratio of kaolin, talcum powder and nano silicon dioxide is 1-3:1-3:0.

5.

7. The high-strength glass fiber reinforced plastic for composite cylindrical shell according to claim 1, characterized in that: The initiator is prepared by mixing tert-butyl peroxy-2-ethylhexanoate and tert-butyl peroxybenzoate, and the mass ratio of tert-butyl peroxy-2-ethylhexanoate to tert-butyl peroxybenzoate is 1:1-3.

8. The high-strength glass fiber reinforced plastic for composite cylindrical shell according to claim 1, characterized in that: The coupling agent is silane coupling agent KH550 or silane coupling agent KH560.

9. The high-strength glass fiber reinforced plastic for composite cylindrical shell according to claim 1, characterized in that: The antioxidant is antioxidant 1010 or antioxidant 1076.

10. The method for preparing high-strength glass fiber reinforced plastic for composite cylindrical shell according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: heating the modified epoxy resin to 120-150°C, stirring at 800-1000 rpm for 1-2 hours, then cooling to 60-80°C, adding an antioxidant and a coupling agent, stirring at 800-1200 rpm for 20-40 minutes, then adding a filler and an initiator, continuing to stir at 1100-1300 rpm for 30-50 minutes, then raising the temperature to 150-170°C, adding glass fiber, stirring at 600-800 rpm for 1-2 hours, and extruding with a screw extruder to obtain the product.

Citation Information

Patent Citations

  • Glass fiber reinforced plastic and preparation method thereof

    CN112812529A

  • Glass fiber reinforced composite plastic

    CN115819994A

  • Modified epoxy resin and glass fiber reinforcement plate prepared based on same

    CN107033328A

  • Glass fiber reinforced modified epoxy resin and preparation method thereof

    CN116285221A

  • Epoxy resin composition for fiber-reinforced composite material, fiber-reinforced composite material using the same and method for producing latter

    JP2016050233A